Didactics of Reading and Writing at University Level: Two Reviews of Jonathan Potter’s Work - Hincapié, Juan Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The aim of this article is to propose, as a didactic strategy for students in the reading and writing process, an introduction to the construction and formulation of reading reports and reviews at university level. Two approaches to Potter’s work (1998) are postulated in the form of an academic review. The first one, of a descriptive nature, seeks to be faithful to the author’s exposition structure and content, whereas the second one, of a critical nature, raises some direct questions about the work at issue and some underlying intentions in the author’s production. It is concluded that in reading and writing processes, didactics enables the construction of thinking and enhance university education processes